Accuracy of early estimation of maturity at a district general hospital. Issue 6306 (12th December 1981) - Brindle, M J
Abstract : The accuracy of routine sonar scanning of patients attending the antenatal clinic of a general hospital before the 19th week of pregnancy was calculated and compared with the potential accuracy of the techniques used. Out of 200 patients who went into labour spontaneously, 164 delivered within nine days of the sonar prediction, and 152 delivered within nine days of the date estimated from the menstrual history. The discrepancy between the mean of the expected date of delivery from the sonar examination and that derived from the menstrual history was 2.24 days. When the two estimations differed by a week or more the sonar estimation was more accurate, and all 44 patients in this group delivered by the sixth day after the sonar prediction. These findings emphasise the need for those providing a similar service to review the accuracy of their own work.